Formação continuada em Matemática para o pedagogo atuante no interior do Estado de São Paulo: sentidos explicitados por professores da Educação Infantil - Alves, Alessandra de Fátima (2018)
The purpose of this research is to understand and analyze the meanings explained in relation to the Mathematics training courses held in 2016 by the pedagogical teachers working in Child Education located in a city in the interior of the state of São Paulo. The research is qualitative. The question that led to this was: "What were the meanings explained in relation to the Mathematics courses held in 2016 by teachers who teach in Early Childhood Education in a context that involves continuing education?" The instruments used for data collection were semi-structured questionnaires and interviews with teachers inserted in the process of continuing training outside working hours in a municipal school. The theoretical reference considers the studies of Leontiev (1978, 1983); Vigotski (2009); Imbernón (2009, 2010, 2011, 2012); Lorenzato (2006, 2011, 2012); Hengemuhle (2008); Vargas (2014), Gladcheff (2015), among others. They stand out in the definition of senses studies pointed out by Leontiev (1978, 1983) and in the continued studies studies of Imbernón (2009, 2010, 2011, 2012). The analysis of the data indicated that the directions explained by the pedagogues refer to: a) methodology; b) mathematical contents. In the methodology teachers emphasized as being fundamental for contribution in teacher training, because it is linked to classroom practice. In the mathematical contents, the explicit meanings are related to what should be taught in Early Childhood Education, being the contents connected with the methodology, which denotes that the relation that the teachers create with the teaching of mathematics is very related to the professional knowledge, reflection of the teaching practices and the sharing of experiences, during the teacher training carried out in the context in which the teacher acts.